2018
DOI: 10.5430/cns.v7n1p21
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ happiness and awareness of their influence on work in governmental and private hospitals

Abstract: Nurses passed through many stressful experiences during nursing work. Emotional support and considering their emotional needs can alleviate such work-associated tension and contribute to the quality of their performance. Nurses’ happiness and awareness of their influence on work are necessary blocks to build the nurses’ emotional steadiness, and thus their work retention and turnover rates would be maintained. This study establishes to attain two aims: First: to identify the levels of nurses’ happiness and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…This suggests that individuals with higher scores on the mental health disorder scale were more likely to report lower levels of happiness. Other studies, including [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], also reported similar findings.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This suggests that individuals with higher scores on the mental health disorder scale were more likely to report lower levels of happiness. Other studies, including [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], also reported similar findings.…”
Section: Discussionsupporting
confidence: 54%
“…Jradi and Abouabbas (2017) conducted a cross-sectional survey of women in Riyadh and found that women experiencing poor physical conditions and violence had impoverished senses of well-being [ 17 ]. Alhakami and Baker (2018) examined happiness among nurses and found a correlation between happiness and awareness of the influence of their work [ 18 ]. Esmail and Shili (2018) gathered questionnaire data to examine the relationship between happiness, social factors, and economic development among people in Jazan, Saudi Arabia, and found that although happiness contributes to economic development via increased motivation, they identified social factors as a main source of happiness, including health care, education, employment, and marital status [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Covid Patient careCovid-19, which is a very big risk for health workers, can certainly reduce the performance of officers in providing health services to patients. According to Alhakami & Baker (2018), nurses face various difficulties in their work, such as work overload, treatment errors, unstable nurse image, decreased work motivation, and work discomfort (Fernandes et al, 2020) stated that the experience of carrying out treatment in pandemic conditions has the potential to cause long-term and short-term consequences for health workers, the social environment and the profession.…”
Section: Introductionmentioning
confidence: 99%